Expression of oxidative stress in metastatic retinoblastomaa comparative study - Mukhopadhyay, S; Dutta, J; Raut, R; Datta, H; Bhattacharyay, A K (Nepalese Journal of Ophthalmology, 2012)
Objective: To compare oxidative stress between primary retinoblastoma and retinoblastoma with distant metastasis. Patients and methods: Forty consecutive patients presented with primary retinoblastoma and the same number of patients presented with distant metastasis, attending the outpatient department of our hospital between August 2002 and April 2005. All the patients with retinoblastoma underwent a standard metastasis workup and were subsequently categorized into two groups (without metastasis and with metastasis).Venous blood samples were drawn from each patient. After proper centrifugation, serum was collected and antioxidant enzymes and reactive oxygen species (ROS) were assayed. Main outcome measures: Serum collected from the patients was subjected to biochemical assay of the antioxidant enzymes (superoxide dismutase, catalase and peroxidise) and ROS to determine any difference in enzyme activity between the two groups. Results: Antioxidant levels were found to be less in the metastasis group as compared to the primary intraocular retinoblastoma group(p<0.05).Mean ROS activity was found to be increased in metastatic group (p<0.05). Conclusion: The decreased antioxidant enzymes level along with increased ROS activity in patients with metastatic retinoblastoma reflect increased oxidative stress as compared to primary intraocular retinoblastoma patients. DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6543 Nepal J Ophthalmol 2012; 4 (2): 271-276